TELAAH KRITIS TERHADAP PENDEKATAN TAFSIR BI AL-MA’TSUR - Aprilita Hajar (LP2M IAIM Sinjai, 2022)
Abstract: this article discusses the study of the approach of Tafsir bi Al-Ma’tsur which uses the method of interpretation of the Qur'an based on history which includes verse by verse, the interpretation of the verse with the sunnah of the Prophet and also the interpretation of the history of the companions and tabiin. As the Times began to emerge some differences of opinion related to the validity of the interpretation of bi Al-Ma'tsur, it should be emphasized that the interpretation of bi Al-Ma'tsur derived from the Qur'an and sunnah sahih assessed marfu’ and must be accepted. While those from the history of friends or tabiin are still disputed, whether they are accepted or not. Although it has many advantages in terms of the source of interpretation, but it can not be avoided and there must be weaknesses that this interpretation of Bil-Ma'tsur. The research method used in this discussion is literature. The urgency or the results of this study can critically examine the approach related to the interpretation of bil-Ma'tsur in which each interpretation has its own characteristics, both in terms of method, value, style, systematics of writing, opinions of scholars’ and so forth.